Evaluation of the Relationship Between Gingival Pigmentation and Smoking - Sena Karacan Çelebi; Ali Ursavaş; Candan Paksoy; Mehmet Esat Başol; Elif Ünsal; Kardelen Başol (Ankara University, 2022)
The abnormal deposition of melanin in the oral mucosa results in melanin pigmentation. The gingiva that has undergone keratinization is most affected. Gingival discoloration may be caused by physiologic or pathological reasons. Melanocytic lesions or melanocytic pigmentations induced by an excessive deposition of melanin in the basal and suprabasal layers of the epithelium are the most common pigmentations of the gingiva. Smoking has been associated to oral melanin pigmentation, particularly in the anterior gingiva. The Fagerstrom Test for Nicotine Dependence is the most used instrument for assessing smoking addiction (FTND). The Fagerstrom Test for Nicotine Dependence (FTND) consists of six questions, with a distinct score assigned to each. Our study comprised 255 individuals over the age of 18 who were smokers, did not use drugs, did not have any systemic illnesses that could contribute to pigmentation, and did not have any active infectious infections. The Hedin scale was used to assess the pigmentation levels of the subjects. The Fagerstrom Test for Nicotine Dependence was used to diagnose the kind of cigarette addiction exhibited by the subjects. Using the Fagerstrom questionnaire, we observed that pigmentation was more common as smoking tendency inreased.